Four-channel sensor-array for the non-contact temperature measurement of liquids in hermetically closed systems - Eder, Cornelia; Becker, Thomas; Delgado, Antonio (Food Control, 2009)
Non-contact thermometers would ideally be suited for temperature control in food industry because they bear no risk of contamination. This paper presents a new method for temperature measurement inside hermetically closed vessels that allows measuring the liquid temperature independent of the superposed thermal radiation of the wall. It solves the problem that conventional pyrometric measurements require a free surface. It extends the range of application of radiation thermometers in food industry extraordinarily. A model of the spectral distribution of the radiant power is given. It includes the temperature distribution and the optical properties of liquid and vessel and proves that the shares of thermal radiation from liquid or container depend on the wavelength. This fact is exploited by a sensor-array. It disposes of four channels with different optical bandwidths that evaluate the thermal radiation emitted by the entire system. The achieved precision is considerably better than the mere determination of the liquid temperature by the outer wall temperature. For polytetrafluorethylen (PTFE), well suited for applications in chemical industry but with weak transparency in mid infrared, the first prototype has an accuracy of 4 K for the worst case with temperature differences between liquid and outer surface of the wall up to 40 K, a 90% improvement to the already existing conventional pyrometers. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.fourch
Keywords: Closed containers; Non-contact temperature measurement; Radiation thermometer; Vacuum distillation